EVALUATION OF STANDARDIZED TESTS - Kenesova Jazira Bauirjan qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article gives information about the standardized tests, its aspects to determine the effectiveness, fairness, and reliability and impact on students' perception of their language level.